تقييم نتائج الكي الكيماوي لضخامة القرينات الأنفية - إبراهيم مصطفى; يوسف يوسف; ياسين عهد (Latakia University Journal -Medical Sciences Series, 2019)
استخدم محلول نترات الفضة في كي القرينات الأنفية المتضخمة بتركيزين 10%، 20% للمقارنة بين الفعالية في الحالتين. طبق تركيز 10% على45 مريضاً وتركيز 20% على 45 مريضاً من كلا الجنسين ممن تتراوح أعمارهم بين 15 - 50 سنة. تمت مراقبة المرضى سريرياً بعد 4أيام، 10أيام, 3أشهر, 6 أشهر من الكي فتم الحصول على النتائج التالية: 1- استعمال محلول نترات الفضة في الكي الكيماوي للقرينات الأنفية المتضخمة أعطى نتائج جيدة من حيث الفعالية, خاصّة بالنسبة للتركيز 20%. 2- تشكل القشور, النزف الخفيف, الالتصاقات مع الوتيرة بعد الكي حدثوا بالنسب: 33.33%, 22.22%, 14.44% على التوالي. 3- نسبة النكس بعد 6أشهر بالتركيز 10% هي 47.22% في حين تبلغ 35% بالتركيز 20%. A solution of silver nitrate of two concentrations 10% and 20% was used in the cautery of nasal hypertrophic turbinates to compare the efficiency in the two cases. The concentration 10% was performed on 45 patients, and 20% was also performed on 45 patients of both sexes, whose ages range between 15-50 years. A clinical follow -up of the patients was performed after 4 days, 10 days, 3 months, and 6 months of the cautery. The results obtained were as follows: 1. The use of silver nitrate solution in the chemical cautery of the nasal hypertrophic turbinates gave good results of efficiency especially for the concentration 20%. 2. Production of crusts, little bleeding, and adhesion with the nasal septum after the cautery happened at the rates: 33.33%, 22.22%, 14, 44%. 3. The average of recurrence after 6 months was 47.22% in the concentration 10%; whereas it was 35% in the concentration 20%.